Pengaruh Faktor Budaya, Faktor Sosisl, Faktor Pribadi dan Faktor Psikologis Terhadap Perilaku Konsumtif Berbelanja Online pada Mahasiswa Fakultas Ekonomi Universitas Pendidikan Ganesha: Indonesia - Crisna Virania Purba; Made Ary Meitriana (Ekuitas: Jurnal Pendidikan Ekonomi, 2025)
His study aims to analyze the influence of cultural factors, social factors, personal factors and psychological factors on online shopping consumer behavior among students of the Faculty of Economics, Ganesha University of Education. This quantitative study uses nonprobability sampling techniques with purposive sampling involving 191 students as respondents. Data analysis was carried out using multiple linear regression analysis techniques. The results of the study indicate that cultural factors have a positive and significant influence on consumer behavior with a significance of 0.000 < 0.05. Social factors have a positive and significant influence on consumer behavior with a significance value of 0.000 < 0.05. Personal factors have a positive and significant influence on consumer behavior with a significance value of 0.000 < 0.05. Psychological factors have a positive and significant influence on consumer behavior with a significance value of 0.000 < 0.05. Simultaneous analysis of cultural, social, personal, and psychological factors significantly influences consumer behavior, as evidenced by the calculated F > F table, which is 21.096 > 2.42, with a significance level of 0.000 < 0.05. These results indicate that all independent variables simultaneously have a significant effect on the dependent variable.